Distributional constraints and efficiency in a tradable permit market - Cathrine Hagem; Hege Westskog (University of Oslo, Department of Economics, 2006)
It is a well known result that taking distributional constraints into account when allocating tradable permits to different agents can lead to an imperfectly competitive permit market. Hence, the emission target is no longer met at least cost. In this paper we suggest an allocation rule for permits which can handle this problem. If the permits are allocated twice during the same period, and the allocation in the second round is dependent on the market price for permits, this allocation rule can achieve both cost effectiveness and meet specific requirements for cost distribution across agents.
Keywords: Q52; Q54; 330; Climate Change; Emission Permits; Allocation; Cost Effectiveness; Distributional Constraints; Umweltökonomik; Wirkungsanalyse; Klimaveränderung; Theorie; Emissionshandel; Verteilungswirkung